The Principal's Visionary Leadership in Developing Multimedia Life Skills for Islamic Boarding School Students - Ahmad Hafi Adzkiya; Ersam Mahendrawan; Surasni (Jurnal Kolaboratif Sains, 2026)
This study aims to analyze the visionary leadership of the school principal in developing students’ multimedia life skills at Pondok Modern An-Nuqthah. The research focuses on the visionary leadership strategies implemented by the principal, human resource management in support of the multimedia program, and efforts to enhance students’ competencies through the development of multimedia skills. The study employs a qualitative approach using descriptive methods. Data were collected through in-depth interviews, observations, and document analysis involving the school principal, teachers, multimedia instructors, and students as research informants. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions, while data validity was tested through source and technique triangulation. The results of the study indicate that the school principal exercises visionary leadership by formulating a vision focused on digital technology proficiency, human resource empowerment, strengthening a culture of innovation, and the continuous development of multimedia training programs. Human resource management is carried out through enhancing teachers’ competencies, collaborating with various stakeholders, and providing multimedia learning support facilities. This program has led to improved multimedia skills, creativity, and the students’ readiness to meet the demands of the digital age. The study’s conclusions indicate that the principal’s visionary leadership plays a strategic role in developing students’ multimedia life skills through targeted, innovative, and sustainable human resource management